SNAKE AND LADDER GAME INTEGRATION IN EFL SPEAKING INSTRUCTION: A DESCRIPTIVE STUDY AT SMAN 1 PAPAR KEDIRI - Jauharoh Nafisah Mutsla Arfila; Agung Wicaksono; Dewi Kencanawati (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2026)
The purpose of this study was to describe how the Snake and Ladder Game was included into speaking training for the eleventh-grade students at SMAN 1 Papar Kediri during the academic year 2025–2026 and to look at how involved the students were in the process. For this study, a qualitative descriptive design was used. Field notes, instructional documentation, and speaking evaluations utilising a grading rubric were used to gather data. The results showed that the Snake and Ladder Game was integrated using a planned process with phases for planning, carrying out, and evaluating. Speaking challenge cards based on Analytical Exposition books were added to the game board to encourage students to make a thesis statement, provide evidence, and address opposing ideas. Students' participation during the implementation demonstrated positive growth in social, emotional, and behavioural domains. Through small-group exercises, the turn-taking system fostered peer connection and scaffolding, encouraged oral participation from all students, and made the classroom more lively and communicative. Students' speaking orientation, however, continued to be primarily focused on the instructor rather than their classmates. This study offers a contextual knowledge of how a classic board game might be effectively included as a senior high school speaking teaching tool.